ELIT PENENTU DALAM PEMBANGUNAN PEDESAAN PERSPEKTIF SIYASAH SYAR’IYYAH: Studi Desa Kembangragi Kecamatan Pasimasunggu Kabupaten Kepulauan Selayar - Syahrul, Syahrul; Kurniati, Kurniati; Rahman, Arif (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
Decisive elites are groups or institutions that have collectivity in influencing the social order of government. This study aims to determine the existence of decisive elites in rural development from the perspective of shar'iyyah siyasah. This research is a qualitative field research with an empirical juridical and normative syar'i approach. The results showed that the decisive elite group in the Selayar Islands Flower Village played a direct role in contributing thoughts, ideas and constructive criticism in determining the direction of development, problem solving and implementation of village activities whose reality was only represented by certain elites, such as political elites, scholars, women, and youth elites. Development in accordance with the principles of shar'iyyah siyasah is participatory development and involves various elements, not dominated by certain groups, but becomes a collective responsibility in accordance with the principle of equality and the principle of deliberation.